Validation of an Ion Torrent Sequencing Platform for the Detection of Gene Mutations in Biopsy Specimens from Patients with Non-Small-Cell Lung Cancer. - Shiro Fujita; Katsuhiro Masago; Jumpei Takeshita; Chiyuki Okuda; Kyoko Otsuka; Akito Hata; Reiko Kaji; Nobuyuki Katakami; Yukio Hirata (PLoS ONE, 2015)
Treatment for patients with advanced non-small cell lung cancer (NSCLC) is often determined by the presence of biomarkers that predict the response to agents targeting specific molecular pathways. Demands for multiplex analysis of the genes involved in the pathogenesis of NSCLC are increasing.We validated the Ion Torrent Personal Genome Machine (PGM) system using the Ion AmpliSeq Cancer Hotspot Panel and compared the results with those obtained using the gold standard methods, conventional PCR and Sanger sequencing. The cycleave PCR method was used to verify the results.The Ion Torrent PGM resulted in a similar level of accuracy in identifying multiple genetic mutations in parallel, compared with conventional PCR and Sanger sequencing; however, the Ion Torrent PGM was superior to the other sequencing methods in terms of increased ease of use, even when taking into account the small amount of DNA that was obtained from formalin-fixed paraffin embedded (FFPE) biopsy specimens.